Assessing the determinants and stability of self-control into adulthood - Diamond, Brie (Criminal justice and behavior, 2016)
The stability hypothesis of Gottfredson and Hirschi?s general theory of crime has received limited support in the literature. However, recent research on the dimensions of self-control suggests varied developmental trends that may conflate the idea of stability. Using a sample of more than 300 individuals from the northeastern United States, this study examines the stability hypothesis across early adulthood and expands the current literature by considering the early childhood risk factors that may distinguish between longitudinal trajectories of self-control. Finally, a reduced, multidimensional version of the behavior problem index for measuring self-control is introduced. Results show evidence of relative stability in three dimensions of self-control, and that sex predicts trajectory group membership. Theoretical implications are discussed.